2016
DOI: 10.1002/anie.201607735
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Cleavage of C=S and P=S Bonds at an AlI Center: Preparation of Terminally Bound Aluminum Sulfides

Abstract: The treatment of cyclic thioureas with the aluminum(I) compound NacNacAl (1; NacNac=[ArNC(Me)CHC(Me)NAr] , Ar=2,6-Pr C H ) resulted in oxidative cleavage of the C=S bond and the formation of 3 and 5, the first monomeric aluminum complexes with an Al=S double bond stabilized by N-heterocyclic carbenes. Compound 1 also reacted with triphenylphosphine sulfide in a similar manner, which resulted in cleavage of the P=S bond and production of the adduct [NacNacAl=S(S=PPh )] (8). The Al=S double bond in 3 can react w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 92 publications
6
58
0
1
Order By: Relevance
“…[30] Analysis of 3 by 77 Se NMR spectroscopy showed as ingle resonance at À381 ppm. TheW iberg bond index (WBI AlSe = 1.39) is greater than the values calculated for II (WBI AlS = 1.20) [10] and III (WBI AlTe = 1.20), [11] both of which claim to be Al = Edouble bonds.These data indicate the presence of significant multiple-bond character in 2,p articularly when the high degree of polarization in this bond is considered (NBO charges:Al=+1.61, Se = À1.06). [24] To further understand the electronic structure of the anions in 2 and 3,D FT calculations were performed at the PBE0/def2-TZVP level of theory.T he optimized geometry for the [Al(NON Ar )(Se)] À anion is in good agreement with the X-ray data, with ac alculated AlÀSe bond length of 2.198 .…”
Section: To Afford the Bridged Telluride Complex [K(thf)] 2 -[(M-te)(mentioning
confidence: 58%
See 1 more Smart Citation
“…[30] Analysis of 3 by 77 Se NMR spectroscopy showed as ingle resonance at À381 ppm. TheW iberg bond index (WBI AlSe = 1.39) is greater than the values calculated for II (WBI AlS = 1.20) [10] and III (WBI AlTe = 1.20), [11] both of which claim to be Al = Edouble bonds.These data indicate the presence of significant multiple-bond character in 2,p articularly when the high degree of polarization in this bond is considered (NBO charges:Al=+1.61, Se = À1.06). [24] To further understand the electronic structure of the anions in 2 and 3,D FT calculations were performed at the PBE0/def2-TZVP level of theory.T he optimized geometry for the [Al(NON Ar )(Se)] À anion is in good agreement with the X-ray data, with ac alculated AlÀSe bond length of 2.198 .…”
Section: To Afford the Bridged Telluride Complex [K(thf)] 2 -[(M-te)(mentioning
confidence: 58%
“…When carbon is replaced with a X 14 elements in conjunction with one of the chalcogenide elements E (E = O, S, Se,T e), a" heavy" carbonyl group is formed (Scheme 1). [7] Most pertinent to this study are compounds containing the Al=E functional group, [8] which have been isolated for E = O, [9] S, [10] and Te [11] (Figure 1). [7] Most pertinent to this study are compounds containing the Al=E functional group, [8] which have been isolated for E = O, [9] S, [10] and Te [11] (Figure 1).…”
mentioning
confidence: 99%
“…[23] Overall, the reaction between complex 3 and 2equiv of PhNCS leads to the formation of an ew C=Cb ond (ketenimine 4)a nd the Au III dithiocarbamate complexes 6 (6' '). Gratifyingly, 5 and 5' ' were the only Au III complexes to form under these conditions.T hey were obtained as a1:1 mixture of stereoisomers and were isolated in ag lobal 68 %y ield.…”
Section: Angewandte Chemiementioning
confidence: 96%
“…This was employed recently by Nikonov and co‐workers to activate the H−H, H−P, H−N, H−O, H−Si, H−B, and H−C σ bonds . More recently, the group of Nikonov also showed that the NacNacAl I complex could activate even stronger σ bonds, such as C−F, C−O, P−P, and C−S, and π bonds, such as C=S and P=S . It is believed that activation proceeds at a single group 13 metal center …”
Section: Introductionmentioning
confidence: 98%